Investigations into mechanisms of complement regulation and bacterial evasion of the innate immune response - Caesar, JJE (2012)
The complement system is a major mechanism of the innate immune system, providing a first line of defence against infection. Many pathogens have evolved mechanisms of evading the complement response by recruitment of complement components onto their surface. Presented here is characterisation of the interface between a complement regulator, factor H, and a protein from Neisseria meningitidis, factor H binding protein (fHbp), which increases complement evasion by the meningococcus. The affinity of the interaction has been measured and experiments have been performed showing that fHbp mimics the glycosaminoglycans found on the surface of host cells. The atomic resolution structure of a mutant form of fHbp that ablates factor H binding is also presented which is a potential vaccine candidate.